Modelagem de sistemas hidrotérmicos interligados utilizando dinâmica de sistemas - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Brazilian energy matrix is composed predominantly hydroelectric generation, this fact makes the country dependent on the inflow regime. The source of additional generation to meet the country's demand in low peak times is the generation of energy from thermal power plants, but increasingly these plants become operational marginal cost of short-term energy rises. The country has a large interconnected power system, it is possible to carry out the exchange of energy between regions, but the decision about dispatch and exchange of energy is a complex task. This decision is made by the National Electric System Operator (ONS) with the help of Newave and Decomp models, but these models are complex and inflexible, besides the slow response to a particular action. Due to this fact, this paper seeks an alternative to aid in the stock test and obtaining future responses from actions taken in the present, with a fast response time. For this is used the system dynamics technique that seeks to model the relationships of cause and effect fed back, to understand its effects on the performance of the system under study. The elaborate model takes into account the main variables that make up the Brazilian electrical system as Energy Affluent Natural (ENA), Generation Instrument, hydro generation, wind generation, power load, stored energy and the Variable Cost per Unit (CVU) of thermal units. The main objectives are to understand the operation of the National Interconnected System, assist in the decision to use water from reservoirs in the present or save for the future and get the consequences of this decision in the Settlement of Differences Price (PLD) and energy exchange between subsystems, and analyze the influence of different scenarios of ENA and wind generation in the system. With the developed model was possible to show the importance of the exchange of energy between the subsystems in order to avoid possible deficit situations. The main standard contribution was obtained by applying ENA scenarios and Generation Wind, with a 10% increase in ENA curve was possible to eliminate various situations with deficit and reduce the PLD, whereas with a 10% reduction in the curve ENA periods with high deficit and the PLD increased significantly.
Keywords: Engenharia; Engenharia elétrica; Sistema de energia elétrica; Sistema hidrotérmico; Engineering; Electrical engineering; Electric power system; Hydrothermal System; CNPQ::ENGENHARIAS